Public Administration Institutions, Access to Public Services, and Homicide Rates: A Cross‐National Analysis - Lance Y. Hunter; William Hatcher; Wesley L. Meares (Politics & Policy, 2026)
ABSTRACT Previous valuable scholarship has examined how numerous political, economic, and social factors affect homicide rates. However, we do not understand how the character of public administration institutions and the equality of access to public services affect homicide rates. Thus, this study examines the relationship between bias in public administration institutions, equality of access to public services, and intentional homicide rates in 142 countries from various levels of development in Africa, Asia, Europe, Latin America, and North America from 1991 to 2021. The results indicate that more biased public administration institutions and less equal access to public services are associated with higher homicide rates. In addition, through conducting a mediation analysis, we find that more biased public administration institutions are associated with greater wealth inequality and higher homicide rates. These results have important implications in considering how the character of public administration institutions and the equality of access to public services affect homicide rates globally. Related Articles Acosta‐González, Nicolás, & Nataly Posso‐Naranjo. 2025. “Crime and Recidivism in Ecuador.” Politics & Policy 53(2): e70030. https://doi.org/10.1111/polp.70030 . Mitchell, Joshua L., & Adam M. Butz. 2019. “Social Control Meets New Public Management: Examining the Diffusion of State Prison Privatization, 1979–2010.” Politics & Policy 47(3): 506–544. https://doi.org/10.1111/polp.12309 . Butz, Adam M., Michael P. Fix, and Joshua L. Mitchell. 2005. “Policy Learning and the Diffusion of Stand‐Your‐Ground Laws.” Politics & Policy 43(3): 347–377. https://doi.org/10.1111/polp.12116 .